195 Maternal Impact on Fetal Muscle and Adipose Tissue Development. (8th October 2021) - Du, Min
Abstract: Tissues and organs are actively developing during the fetal stage, which is sensitive to nutritional alteration and exerts long-term impacts on offspring performance. Both muscle and adipose tissue are derived from the dermomyotome during the early embryonic stage, and their common origins provide an opportunity to promote myogenic instead of adipogenic differentiation, which enhances the lean/fat ratio of offspring. In previous studies with sheep and cattle, we found that maternal nutrient deficiency reduces fetal myogenesis and the lean/fat ratio of offspring. Stress is common in animals during pregnancy, and we examined the impacts of maternal stress induced by dexamethasone on fetal muscle and adipose development. We found that maternal stress impairs fetal muscle and brown adipose tissue (BAT) development. Mechanistically, we found that maternal stress suppresses mitochondrial biogenesis during fetal muscle and BAT development by elevating DNA methylation in the promoter of peroxisome proliferator-activated receptor-gamma coactivator α (PGC-1α), which persists in offspring muscle and BAT, generating lasting effects on the functions of muscle and adipose tissue. In short, available data clearly show that maternal nutrition and other physiological factors have profound impacts on fetal development, which programs offspring performance. Understanding related mechanisms are important for effective and precise management of animals during gestation in order to enhance production efficiency of offspring.